ADVOCATE ROLE IN THE CASE OF CRIMINAL ACCOMPANY CLIENTS - Muhammad Amri Amir; Hambali Thalib; M. Kamal Hidjaz (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal